S‐1 plus Raltitrexed for Refractory Metastatic Colorectal Cancer: A Phase II Trial. (16th January 2019) - Chen, Ye; Wu, Jing; Cheng, Ke; Li, Zhi‐Ping; Luo, De‐Yun; Qiu, Meng; Gou, Hong‐Feng; Yi, Cheng; Li, Qiu; Wang, Xin; Yang, Yu; Cao, Dan; et al.
Abstract: Lessons Learned: The upregulation of dihydropyrimidine dehydrogenase (DPD) and thymidylate synthase (TS) are important mechanisms of resistance to 5‐fluorouracil (5‐FU) in metastatic colorectal cancer (mCRC) after long exposure to 5‐FU. S‐1 (containing a DPD inhibitor) combined with raltitrexed (a TS inhibitor) showed a moderate effect, which needs further study as a third‐ or later‐line therapy in mCRC. Background: 5‐fluorouracil (5‐FU) is a fundamental drug in the treatment of metastatic colorectal cancer (mCRC). Patients with mCRC are often exposed to 5‐FU and/or its analogues for a long time because of its central role in treatment regimens. The upregulation of dihydropyrimidine dehydrogenase (DPD) and/or thymidylate synthase (TS) are important mechanisms of resistance of 5‐FU. To evaluate the efficacy and safety of S‐1 (containing a DPD inhibitor) and raltitrexed (a TS inhibitor) for refractory mCRC, a one‐center, single‐arm, prospective phase II trial was conducted. Methods: Patients who had mCRC that had progressed after treatment with fluoropyrimidine, irinotecan, and oxaliplatin and who had at least one measurable lesion were eligible for this trial. Patients received oral S‐1 (80–120 mg for 14 days every 3 weeks) plus an intravenous infusion of raltitrexed (3 mg/m 2 on day 1 every 3 weeks). The primary endpoint was objective response rate (ORR). Secondary endpoints included progression‐free survival (PFS), overall survival (OS), and toxicity. Results: In total, 46 patients were enrolled. Three patients did not complete the first assessment because of adverse events and unwillingness, leaving tumor response evaluation available in 43 patients. Of 43 evaluable patients, the ORR was 13.9% and disease control rate was 58.1%. In the intention‐to‐treat population ( n = 46), the ORR was 13.0% and disease control rate was 54.3%. Median PFS and median OS were 107 days (95% confidence interval [CI], 96.3–117.7) and 373 days (95% CI, 226.2–519.8), respectively. Most of the adverse effects were mild to moderate. Conclusion: S‐1 combined with raltitrexed for refractory mCRC showed moderate effect, and it is worthy of further study as third‐ or later‐line therapy in mCRC.